2017
DOI: 10.1155/2017/9854184
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fe Doping on the Magnetic and Magnetocaloric Properties of Mn5−xFexGe3

Abstract: The magnetic and magnetocaloric properties of a series of minutely doped Mn5-xFexGe3 compounds that exhibit the D88-type hexagonal crystal structure at room temperature have been investigated. For all Fe concentrations, the alloys are ferromagnetic and undergo a second-order ferromagnetic-to-paramagnetic transition near room temperature. Although the small Fe doping had little effect on the ferromagnetic transition temperatures of the system, changes in the saturation magnetization and magnetic anisotropy were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Liu et al [23] found that the Curie temperature and isothermal magnetic entropy decrease as Ga content increase, while the magnetic moment reaches a maximum around x = 0.6 by studying the effect of Ga content in Mn 5 Ge 3−x Ga x on the MCE. Moreover, the magnetocaloric properties were previously researched for some Mn 5 Ge 3 -based off-stoichiometric alloys, such as Mn 5 Ge 3−x Ag x [24], Mn 5−x Co x Ge 3 [25], Mn 4.75 Ge 3 (Co, Fe) 0.25 [26], Mn 5−x Fe x Ge 3 [27], Mn 5+x Ge 3−x [28], Mn 5−x Ge 3 Ni x [29] and few others [30][31][32]. Although recent studies have reported magnetocaloric properties in these materials, a thorough study of the critical behavior near the phase transition temperature is indispensable for a better understand of the effect of doping on the MCE of the material.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [23] found that the Curie temperature and isothermal magnetic entropy decrease as Ga content increase, while the magnetic moment reaches a maximum around x = 0.6 by studying the effect of Ga content in Mn 5 Ge 3−x Ga x on the MCE. Moreover, the magnetocaloric properties were previously researched for some Mn 5 Ge 3 -based off-stoichiometric alloys, such as Mn 5 Ge 3−x Ag x [24], Mn 5−x Co x Ge 3 [25], Mn 4.75 Ge 3 (Co, Fe) 0.25 [26], Mn 5−x Fe x Ge 3 [27], Mn 5+x Ge 3−x [28], Mn 5−x Ge 3 Ni x [29] and few others [30][31][32]. Although recent studies have reported magnetocaloric properties in these materials, a thorough study of the critical behavior near the phase transition temperature is indispensable for a better understand of the effect of doping on the MCE of the material.…”
Section: Introductionmentioning
confidence: 99%
“…This compound, owing to its physical properties, may be used in magnetic refrigerators [39,40]. The attractive properties of Mn 5 Ge 3 initiated studies of, for example, off-stoichiometric Mn 5+x Ge 3-x alloys [41] or systems modified chemically by introducing elements such as Co [42][43][44][45], Fe [42,[44][45][46][47], or Ni [48] into the Mn position or by replacing Ge with Si [49,50], Ga [51], Sb [52], Al [53], Ag [54,55], or even Fe [56]. Moreover, simultaneous substitutions of Fe for Mn and Si for Ge have also been attempted [57,58].…”
Section: Introductionmentioning
confidence: 99%